2019
DOI: 10.5539/hes.v10n1p16
|View full text |Cite
|
Sign up to set email alerts
|

Use of Self-Assessment of Video Recording to Raise Students’ Awareness of Development of Their Oral Presentation Skills

Abstract: This paper aims to examine if using video recordings help students raise their awareness of the development of their oral presentation skills by reviewing video recordings of their presentations. For this study, all students who took a Financial Accounting class in the academic year 2018–2019 at Lincoln University (LU) were video-recorded when presenting. Participants were asked to review their video recordings, assess their performance, and record their reflections by using a Self-Assessment Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Consequently, self-assessment enhances their self-reflection and adjustment. Some studies have shown that creating video raise students’ awareness of self-assessment by viewing a created video and improves learning performance in the oral presentation ( Ritchie, 2016 ; Tailab and Marsh, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, self-assessment enhances their self-reflection and adjustment. Some studies have shown that creating video raise students’ awareness of self-assessment by viewing a created video and improves learning performance in the oral presentation ( Ritchie, 2016 ; Tailab and Marsh, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Explicitly indicated goals and learning aims encourage the accomplishment of anticipated results. Research reveals the necessity for the formation of precise goals and for clearness in indicating learning objectives to be examined (Tailab & Marsh, 2020;Peltier, Scovotti, & Pointer, 2008;Rohm, Stefl, & Ward, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Every listener completed assessment rubrics for the presentation, and they recognized the strengths and weaknesses of the presentation. Besides, the presentation was filmed, and every student conducted a self-examination (Tailab & Marsh, 2020). Subsequently, the submission of the self-assessment scorings, a typed conclusion of the audience's responses, and evaluation were offered to the presenter.…”
Section: Business To Business Marketing (Undergraduate Seniors)mentioning
confidence: 99%
See 2 more Smart Citations